Comprehensive Bioinformatics Analysis of Tooth Agenesis: Identifying Key Genes, Regulatory Networks, and Potential Therapeutic Targets - Kumar, S.Aravind (Journal of Neonatal Surgery, 2025)
Background: Tooth agenesis represents one of the most prevalent developmental anomalies in humans, affecting approximately 2-10% of the global population. Understanding the molecular mechanisms underlying this condition is crucial for developing targeted therapeutic interventions. Objective: This study aimed to identify and characterize the key genes associated with tooth agenesis through comprehensive bioinformatics analysis, including gene ontology enrichment, pathway analysis, protein-protein interaction networks, and drug target identification. Methods: We utilized the DisGeNET database to identify the top 10 genes associated with tooth agenesis based on Gene-Disease Association scores. Subsequently, we performed enrichment analysis using ENRICHR platform to examine Gene Ontology biological processes, cellular components, and molecular functions. MicroRNA targets were identified using TargetScan and miRBase databases. Protein-protein interaction networks were constructed to identify hub proteins, and potential drug targets were explored through IDG drug target analysis. Results: WNT10A emerged as the most significant gene (scoreGDA: 0.8), followed by BMP4 (0.7) and LRP6 (0.65). Enrichment analysis revealed significant involvement in lipoprotein particle clearance, steroid metabolic processes, and cholesterol transport pathways. The protein-protein interaction network identified key hub proteins involved in cellular signaling cascades. Several potential therapeutic targets were identified, with Baricitinib showing the highest significance as a potential treatment option. Conclusion: This comprehensive analysis provides valuable insights into the molecular mechanisms of tooth agenesis, highlighting potential therapeutic targets and pathways that could inform future treatment strategies for this developmental disorder.